(untitled) (Impetus, 2021)
At present obesity is present as a public health disorder, no longer of an isolated or common order in the upper strata, excess weight is a chronic disease affecting any socioeconomic stratum and presenting mortal ailments, cardiovascular diseases and diabetes. Physical inactivity has also led to a totally sedentary life, thus linked to an increased risk of diseases. Presenting in this way physical inactivity linked to sedentary lifestyle, non-communicable degenerative diseases within them obesity, workloads, strss and the work environment in which an individual operates are attached, which has led to absenteeism from work, poor performance, conditions in worker integrity, physical fitness and, as has been said before, health.